Διερευνώντας τη χρήση της Αγγλικής γλώσσας ως μέσo στη διδασκαλία της Ελληνικής σε πρόσφυγες και μετανάστες - Μιχαλαρέα, Βιργινία (2019)
The aim of the present research is to examine the experiences of educators and volunteers of refugees and immigrants in their efforts to cope with a new challenge, the teaching of Greek as a foreign language to special populations such as refugees and immigrants. The purpose of this research focuses on the examination of the use of another language as a medium of teaching Greek, but also as a medium of communication with learners. Particular emphasis is placed on the teaching methods followed by other refugee host countries, but also on problems encountered by educators and volunteers. The bibliographic review will compare the experiences of different educators and volunteers and will serve as a useful future tool for anyone involved in refugee and migrant education. The method of approach employed is research. The educators and volunteers involved in this research are sent a questionnaire, which is distributed electronically. The questionnaire analysis is performed through a descriptive analysis with the use of the IBM v.24 SPSS statistical software, where statistically significant data are generated. The sample of the survey is comprised of 60 educators and volunteers of refugees and immigrants, (46 women and 14 men) aged 25-60. The results showed a significant contribution of the English language to the teaching of Greek making its use maximal and inevitable. The educational background (42%) of the majority of learners has not completed primary education. 52.5% of the respondents stated they use English when they pose questions during teaching. 75% of the educators and volunteers claimed that the answers to the questions are in both languages. This contrasts with the 48.6% of the respondents who choose the English language for instructions on an exercise or subject that is being discussed in class.